McHale's navy - Spicer, Bryan; Arnold, Tom, 1959-; Grier, David Alan, 1955 June 30-; Stockwell, Dean, 1938-; Curry, Tim.; Universal Pictures (Firm); Universal Studios Home Video (Firm) (Universal City, CA : Universal Home Video, 1997)
Retired naval commander Quinton McHale's days are dashed when his former nemesis threatens his beloved island base.
Rated PG.
Originally released as motion picture.
Closed-captioned for the hearing impaired.
Based on the television show.
Tom Arnold, David Alan Grier, Dean Stockwell, Tim Curry.
VHS.
Keywords: Feature films; Comedy films; Video recordings for the hearing impaired